Respuesta :

y1 - y2 / x1 - x2

-1 - 5 / 2 - 4

-6/-2

3

y = mx + b

-1 = 3(2) + b

-1 = 6 + b

-7 = b

y = 3x - 7

Hope this helps! ;)

Answer:

The equation is [tex]3x -y =7[/tex]

Solution:

Let us assume that the [tex](x_1, y_1) = (4,5)[/tex] and [tex](x_2, y_2) = (2,-1)[/tex]

The slope of the line m is [tex]=\frac{y_2-y_1}{x_2-x_1}=\frac{-1-5}{2-4}=\left(\frac{6}{2}\right)=3[/tex]

We know the equation of a line at a given point [tex](x_1,y_1) is (y-y_1) = m(x-x_1)[/tex]

Let me take the point (4,5) here,

So the equation of the line is  

[tex](y-5)=3 \times(x-4)[/tex]

[tex]y-5=3 x-12[/tex]

[tex]3x-12 - y+5 = 0[/tex]

[tex]3x -y -7 =0[/tex]

[tex]3x -y =7[/tex]

So, the equation is [tex]3x-y =7[/tex]